Toxicological and Medical Aspects of Aspergillus-Derived Mycotoxins Entering the Feed and Food Chain - Ráduly, Zsolt; Szabó, László; Madar, Anett; Pócsi, István; Csernoch, László (Frontiers in Microbiology, 2020)
Due to Earth’s changing climate, the ongoing and foreseeable spreading of mycotoxigenic Aspergillus species has increased the possibility of mycotoxin contamination in the feed and food production chain. These harmful mycotoxins have aroused serious health and economic problems since their first appearance. The most potent Aspergillus-derived mycotoxins include aflatoxins, ochratoxins, gliotoxin, fumonisins, sterigmatocystin, and patulin. Some of them can be found in dairy products, mainly in milk and cheese, as well as in fresh and especially in dried fruits and vegetables, in nut products, typically in groundnuts, in oil seeds, in coffee beans, in different grain products, like rice, wheat, barley, rye and frequently in maize and, furthermore, even in the liver of livestock fed by mycotoxin contaminated forage. Though the mycotoxins present in the feed and food chain are well documented the human physiological effects of mycotoxin exposure are not yet fully understood. It is known that mycotoxins have nephrotoxic, genotoxic, teratogenic, carcinogenic, and cytotoxic properties and, as a consequence, these toxins may cause liver carcinomas, renal dysfunctions, and also immunosuppressed states. The deleterious physiological effects of mycotoxins on humans are still a first-priority question. In food production and also in the case of acute and chronic poisoning, there are possibilities to set suitable food safety measures into operation to minimize the effects of mycotoxin contaminations. On the other hand, preventive actions are always better, due to the multivariate nature of mycotoxin exposures. In this review, the occurrence and toxicological features of major Aspergillus-derived mycotoxins are summarized and, furthermore, the possibilities of treatments in the medical practice to heal the deleterious consequences of acute and/or chronic exposures are presented.